The Role of Shadow Banking in the Monetary Transmission Mechanism and the Business Cycle - Falk Mazelis (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper investigates the heterogeneous impact of monetary policy shocks on financial intermediaries. I distinguish between traditional banks and shadow banks based on their ability to raise debt and equity funding. The functional form for both intermediaries imposes no constraints ex ante, but a Bayesian estimation of key parameters results in traditional banks having a comparative advantage at raising debt while shadow banks are better at raising equity. In line with empirical observations, shadow bank lending moves in the opposite direction to bank lending following monetary policy shocks, which mitigates aggregate credit responses. The recognition of a distinct shadow banking sector results in an amplified propagation of real shocks and a muted propagation of financial shocks. This identification can help in assessing effects of financial regulation on the economy. A historical shock decomposition highlights the roles of traditional banks and shadow banks in the run-up to the 2008 financial crisis.
Keywords: E32; E44; G20; 330